Structural design for modular integrated construction with parameterized level set-based topology optimization method. (June 2021) - Wei, Peng; Liu, Yang; Dai, Jian-Guo; Li, Zuyu; Xu, Yufeng
Abstract: Modular integrated construction (MIC) can realize modular production in factories and has the advantages of increasing material utilization, speeding up construction, and improving construction environment, which make it more and more widely accepted in engineering practice. But a critical issue for MIC is how to design standard structural modular to maximize its construction productivity. In this paper, a structural topology optimization method based on a parameterized level set is adopted to realize the modular design for stiffness maximum problem of structures. By introducing the symmetry and pattern repetition (SPR) constraints in the optimization model and combining the finite element-based numerical analysis method, the modular design of a structure can be obtained through topology optimization. As a result, the structure can be assembled with repeated modular of the same topology to realize the MIC. Several two-dimensional (2D) and three-dimensional (3D) numerical examples are studied to illustrate the effectiveness of the proposed method in building designs following the MIC concept.